2006
DOI: 10.1089/thy.2006.16.89
|View full text |Cite
|
Sign up to set email alerts
|

Primary Squamous Cell Carcinoma of the Thyroid: Report of Ten Cases

Abstract: PSCCT is an aggressive cancer with death occurring within the first year in most patients. The prognosis for patients with PSCCT is worse than SSCCT. p21, MIB-I, and p53 are overexpressed in PSCCT. Thyroglobulin and TTF can show focal positivity in PSCCT distinguishing it from SSCCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
103
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 14 publications
7
103
1
4
Order By: Relevance
“…Previous studies demonstrated that SCC of the thyroid and PC with an SCC component shows an adverse prognosis [3][4][5][6][7][8][9]. Booya et al showed that the mean surival period was 8.6 months, which was similar to other reports [9].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies demonstrated that SCC of the thyroid and PC with an SCC component shows an adverse prognosis [3][4][5][6][7][8][9]. Booya et al showed that the mean surival period was 8.6 months, which was similar to other reports [9].…”
Section: Discussionsupporting
confidence: 71%
“…Booya et al showed that the mean surival period was 8.6 months, which was similar to other reports [9]. Therefore, multimodal therapy including surgery, chemotherapy, and EBRT is recommended, but, to date, no established protocols for chemotherapy effective for SCC of the thyroid and PC with an SCC component are available.…”
Section: Discussionsupporting
confidence: 67%
“…2,3 Several series have reported a higher incidence in women. 2,3 Presentation and course are similar to that of anaplastic thyroid carcinoma. A rapidly enlarging neck mass and hoarseness are common presenting complaints.…”
mentioning
confidence: 67%
“…This makes a proportion calculation for the surgical treatment, whether a debulking surgery or a curative procedure has been carried out, impossible. Since airway compromise is generally the cause of death in the majority of patients [16], resection and primary reconstruction of the trachea invaded by carcinoma should be tried in the absence of extensive metastases when technically feasible. This offers prolonged palliation, avoidance of suffocation due to bleeding or obstruction [32].…”
Section: Discussionmentioning
confidence: 99%
“…The first primary SCC case was reported by von Karst in 1858. However, approximately 150 cases have been published until recently in the English literature [8,[10][11][12][13][14][15][16]. The tumor behaves aggressively and is clinically identical to an undifferentiated thyroid cancer.…”
mentioning
confidence: 99%